Psikoedukasi Pencegahan Kekerasan Seksual pada Siswa Sekolah Kristen Yusuf - Sahrani, Riana; Dewi, Fransisca Iriani Roesmala; Basel, Wiwin Charolina Putri; Kirana, Liuciana Handoyo (Universitas Negeri Padang, 2025)
Sexual violence is a serious problem in society, which is also an issue of gender equality, which occurs in the environment including in educational institutions. The lack of sex education and the culture of taboo in society has led to the concept of sexual violence. The negative impact of sexual violence behavior also cannot be ignored because it causes physical, mental, social and material injuries and losses. Related to the increasing cases of sexual violence, especially in educational institutions, the PKM Team of Tarumanagara University conducted psychoeducation as an effort to prevent sexual violence in adolescent students at school. The purpose of psychoeducation is to increase students' awareness of the dangers and ways to prevent sexual violence, as well as to create a safe and comfortable environment at school. The seminar participants were 200 students from Kristen Yusuf Junior and Senior High School. The results of the PKM are that students understand what sexual violence is, what forms it takes, how to prevent, and overcome so as not to become victims or perpetrators of sexual violence. The evaluation of this seminar is that the students hope to apply this in their daily lives. The implication of this seminar is that an intervention, such as sex education psychoeducation, can be made to tackle the problem of sexual violence, especially in the school environment.